(untitled) (El-Wahat Journal for Research and Studies, 2023)
Abstract: This article highlights the Thatcher era in British politics mainly the urban policy. This era is defined by most academics as the “Thatcherite” era and as a revolution in British history because of Margaret Thatcher’s long leadership of the Conservative party, first as leader of the opposition between 1975 and 1979, then as prime minister between 1979 and 1990. This decade will always be remembered in Great Britain as the decade of “Thatcherism” and the rising of neoliberalism. Thatcher attracted attention because of her promotion of neoliberalism as a new concept for ruling the country. The widespread use of Thatcherism confirms this view. Margaret Thatcher not only presided over Conservatives success, she personified it. Her election as leader of the conservative party in 1975 came to stand for a new neoliberal ideology, and a distinctive political style and programme of policies. Key Words: neoliberalism, Thatcherism, capitalism, urban policy, city الملخص: يسلط هذا المقال الضوء على حقبة تاتشر في السياسة البريطانية وخاصة السياسة الحضرية. يعرّف معظم الأكاديميين هذه الحقبة بأنها حقبة "تاتشرت" كذلك كثورة في التاريخ البريطاني بسبب قيادة مارغريت تاتشر الطويلة لحزب المحافظين، أولاً كزعيمة للمعارضة بين عامي 1975 و1979، ثم كرئيس للوزراء بين عامي 1979 و1990. هذا العقد يتم تذكره دائمًا في بريطانيا العظمى على أنه عقد "التاتشرية" وصعود الليبرالية الجديدة. جذبت تاتشر الانتباه بسبب ترويجها لليبرالية الجديدة كمفهوم جديد لحكم البلاد. الاستخدام الواسع النطاق للتاتشرية يؤكد هذا الرأي. مارغريت تاتشر لم تترأس نجاح المحافظين فحسب، بل جسدته. جاء انتخابها كزعيم للحزب المحافظ في عام 1975 إلى قيام أيديولوجية نيوليبرالية جديدة، وأسلوب سياسي متميز وبرنامج للسياسات خاصة بالنسبة للتطور الحضري و المدينة . كلمات دالة: النيوليبرالية، التاتشرية ،الرأسمالية ، السياسة الحضرية،المدينة.